1989
DOI: 10.1002/neu.480200403
|View full text |Cite
|
Sign up to set email alerts
|

Androgens modulate endplate size and ACh receptor density at synapses in rat levator ani muscle

Abstract: The dorsal bulbocavernosus or "levator ani" muscle of the rat is highly responsive to androgens. Both the muscle and the motoneurons which innervate it contain high concentrations of androgen receptors. The neuromuscular synapses in this muscle are also affected by changing androgen levels. In particular, the total number of ACh receptors (AChRs) in the muscle is lower in males that have been castrated, and it increases after treatment with the androgens, testosterone and 5 alpha-dihydrotestosterone. An examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 42 publications
2
24
1
Order By: Relevance
“…A positive correlation between androgen levels and muscle fiber size has also been shown in sexually dimorphic, androgen-sensitive muscles in other vertebrate classes. Castration causes a decrease in fiber size that is reversible with testosterone treatment in rat bulbocavernosus muscles (Bleisch and Harrelson, 1989;Balice-Gordon et al, 1990), songbird syringeal muscles (Luine et al, 1980), and guinea pig temporalis muscles (Papanicolau and Falk, 1938;Kochakian et al, 1956).…”
Section: Effects Of Testosterone On Muscle Fiber Propertiesmentioning
confidence: 93%
“…A positive correlation between androgen levels and muscle fiber size has also been shown in sexually dimorphic, androgen-sensitive muscles in other vertebrate classes. Castration causes a decrease in fiber size that is reversible with testosterone treatment in rat bulbocavernosus muscles (Bleisch and Harrelson, 1989;Balice-Gordon et al, 1990), songbird syringeal muscles (Luine et al, 1980), and guinea pig temporalis muscles (Papanicolau and Falk, 1938;Kochakian et al, 1956).…”
Section: Effects Of Testosterone On Muscle Fiber Propertiesmentioning
confidence: 93%
“…In addition, there is strong evidence for the fact that testosterone via its receptor may regulate the coupling mechanisms between Ca v2.2 channels and neurotransmitter release at the neuromuscular junctions of bulbocavernosus and levator ani muscles motoneurons (Nudler et al, 2005). Earlier results have shown that testosterone deprivation reduces the junctional acetylcholine receptor density and androgens modulate endplate size and acetylcholine ACh receptor density at synapses in rat levator ani muscle (Bleisch and Harrelson, 1989;Bleisch et al, 1982;Souccar et al, 1991). Finally, in Xenopus laevis, females have stronger laryngeal synapses than males, and synapse strength is estrogen dependent and the laryngeal neuromuscular synapse is the final effector for sexually differentiated song production.…”
Section: Genetic and Age-linked Alterations In Lactate Homeostasis Unmentioning
confidence: 99%
“…These anabolic effects of androgens involve changes in perineal muscle fiber size, without a change in fiber number (Venable, 1966). Androgens in adulthood also maintain BC/LA neuromuscular junction size (Bleisch and Harrelson, 1989;Balice-Gordon et al, 1990;Lubischer and Bebinger, 1999), acetylcholine receptor number (Bleisch et al, 1982;Bleisch and Harrelson, 1989), and peripheral nerve activity (Fargo et al, 2003).…”
Section: Hormone Dependence Of the Bc/la Muscles In Adulthoodmentioning
confidence: 99%